The cooperation of the International monetary fund (IMF) with Ukraine - Ryabukha, Alexander; Trygub, Inna (My University, 2014)
Continued cooperation between Ukraine and the IMF under present circumstances is reasonable and justified because in terms of tactics: IMF loans are cheaper than those involved in the global financial markets; interaction with the IMF insure the flow of funds to Ukraine from other lenders and investors. Cooperation with the IMF allows Ukraine to use advisory, expert and analytical services IMF. Безперервна кооперація між Україною і IMF при теперішніх обставинах розумна і виправдана, тому що в рамках тактики позики МВФ дешевші, ніж ті, що залучені в глобальні фінансові ринки; взаємодія з IMF страхує потік фондів до України від інших кредиторів і інвесторів. Кооперація з IMF дозволяє Україні використовувати поради експертів т і аналітиків МВФ.
Keywords: еconomic activity; quota; stage; goal; program; економічна діяльність; квоти; стадія; мета; програма; экономическая деятельность; стадия; программа; цель; кафедра ділової іноземної мови та міжнародної комунікації; квоты